2016
DOI: 10.3389/fimmu.2016.00356
|View full text |Cite
|
Sign up to set email alerts
|

HIV Latency-Reversing Agents Have Diverse Effects on Natural Killer Cell Function

Abstract: In an effort to clear persistent HIV infection and achieve a durable therapy-free remission of HIV disease, extensive pre-clinical studies and early pilot clinical trials are underway to develop and test agents that can reverse latent HIV infection and present viral antigen to the immune system for clearance. It is, therefore, critical to understand the impact of latency-reversing agents (LRAs) on the function of immune effectors needed to clear infected cells. We assessed the impact of LRAs on the function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 50 publications
7
49
1
Order By: Relevance
“…However, a full understanding of the optimal dosing schedule for romidepsin and its interaction with immunotherapies is still lacking. As we have previously shown for both CD8 and NK cell function in earlier VOR studies (19,33), in this study, we observed no significant effect of VOR on CD8 immune function after repeated dosing in vivo.…”
Section: Methodssupporting
confidence: 78%
“…However, a full understanding of the optimal dosing schedule for romidepsin and its interaction with immunotherapies is still lacking. As we have previously shown for both CD8 and NK cell function in earlier VOR studies (19,33), in this study, we observed no significant effect of VOR on CD8 immune function after repeated dosing in vivo.…”
Section: Methodssupporting
confidence: 78%
“…However, a range of novel approaches to achieve HIV latency reversal are under study (37,38). Thus, in a similar way, future work must address the effect of novel latency-reversing agents (LRAs) on NK-mediated clearance, given that antigen presentation or ligand modulation might be altered by host-targeted LRAs (39). Of interest, there is evidence that HDAC inhibitor exposure upregulates the surface expression of ligands for activating receptors in NK cells (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrating diverse responses of infected cells to LRAs point to their weak effect (Archin et al, 2012;Spivak et al, 2014;Elliott et al, 2015) and highlight the diversity of determinants responsible for the reservoirs' heterogeneity that were demonstrated so far to be virus genetic background- (Norton et al, 2019), cell model- (Spina et al, 2013), cell type- (Baxter et al, 2016;Grau-Expósito et al, 2019;Kula et al, 2019), silencing mechanism- (Elliott et al, 2014;Yukl et al, 2018), tissue reservoir- (Elliott et al, 2014;Telwatte et al, 2018;Yukl et al, 2018), integration site- (Chen et al, 2017;Abner et al, 2018;Battivelli et al, 2018), patient- (Darcis et al, 2017;Yukl et al, 2018), and gender- (Das et al, 2018) specific. In addition, some studies demonstrate a heterogeneous effect of LRAs on NK cells (Garrido et al, 2016) and cytotoxic T-cell lymphocyte (Walker-Sperling et al, 2016) activity with conflicting observations, suggesting either an immunosuppressive effect or a reduced impact of LRA activity on cells sensing HIV-1 reactivation (Archin et al, 2012;Jones et al, 2014;Clutton et al, 2016;Walker-Sperling et al, 2016;Desimio et al, 2017Desimio et al, , 2018. Moreover, prolonged ART treatment is associated with a significant reduction in the frequency of HIV-1-specific CD8 + T-cells (Gray et al, 1999;Casazza et al, 2001).…”
Section: Resultsmentioning
confidence: 99%